2013
DOI: 10.1088/0967-3334/34/6/713
|View full text |Cite
|
Sign up to set email alerts
|

Length and activation dependent variations in muscle shear wave speed

Abstract: Muscle stiffness is known to vary as a result of a variety of disease states, yet current clinical methods for quantifying muscle stiffness have limitations including cost and availability. We investigated the capability of shear wave elastography (SWE) to measure variations in gastrocnemius shear wave speed induced via active contraction and passive stretch. Ten healthy young adults were tested. Shear wave speeds were measured using a SWE transducer positioned over the medial gastrocnemius at ankle angles ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 34 publications
7
62
0
Order By: Relevance
“…After the SS maneuver with the hip in flexion and the knee in extension, the percentage change in the shear elastic modulus was the greatest in the SM, despite ST, SM, and BF muscles having the same function (i.e., hip extension and knee flexion). Strong linear relationships have been found between the shear elastic modulus measured by ultrasound shear wave elastography and passive tension applied to the muscle (Chernak et al, 2013;Koo et al, 2013). In the current study, shear elastic modulus of the SM was the highest when the knee was flexed at 45 (i.e., in the extension position) for both the PRE and POST conditions.…”
Section: Pre Postsupporting
confidence: 51%
“…After the SS maneuver with the hip in flexion and the knee in extension, the percentage change in the shear elastic modulus was the greatest in the SM, despite ST, SM, and BF muscles having the same function (i.e., hip extension and knee flexion). Strong linear relationships have been found between the shear elastic modulus measured by ultrasound shear wave elastography and passive tension applied to the muscle (Chernak et al, 2013;Koo et al, 2013). In the current study, shear elastic modulus of the SM was the highest when the knee was flexed at 45 (i.e., in the extension position) for both the PRE and POST conditions.…”
Section: Pre Postsupporting
confidence: 51%
“…Here we chose to include all visible tendon tissue in our ROI sub-regions, extending to borders with adjacent tissues. This may introduce error because tendon wave speeds are considerably higher than wave speeds in adjacent tissues such as muscle (Arda et al 2011; Chernak et al 2013). Both the wave guiding and spatial averaging effects on SWS error would be lessened in larger tendons, such that there is potential for obtaining more reliable SWS measures in a larger animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound SWE (specifically with the Supersonic Imagine Aixplorer system) has seen use in multiple clinical domains, including imaging for possible tumors (Wang et al 2012) and lesions (Athanasiou et al 2010) in breast tissue, in addition to the evaluation of liver fibrosis (Bavu et al 2011). Numerous in vivo SWE analyses have been performed in tendon and muscle as well (Akagi & Takahashi 2013; Aubry et al 2013; Aubry et al 2015; Bouillard et al 2012; Brum et al 2014; Chen et al 2013; Chernak et al 2013; DeWall et al 2014b; Eby et al 2014; Gennisson et al 2010; Hug et al 2013; Kot et al 2012; Nakamura et al 2014; Yeh et al 2014; Yoshitake et al 2014), but these tissues present some unique challenges due to their inherent anisotropy. Recent studies have shown that shear wave speeds are dependent on both fiber-direction and load, with load effects arising from the strain stiffening behavior of tendinous tissues (Aubry et al 2013; DeWall et al 2014b; Yeh et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, muscle elasticity has recently been quantified using shear wave ultrasound elastography Takahashi 2013, 2014;Chernak et al 2013;Maher et al 2013;Nakamura et al 2014). Kuo et al (2013) determined neck muscle stiffness using shear wave ultrasound elastography and found that patients with chronic neck pain symptoms had a significantly stiffer trapezius muscle.…”
Section: Introductionmentioning
confidence: 99%